Clinical characteristics and survival outcomes in patients with primary ovarian carcinoid: A historical cohort study - Shujun Kong; Jianan Sun; Xiaolong Sui; Shuaizhi Zhang; YuanBao Qi; Yuanxu Ma; Sijian Li (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Primary ovarian carcinoids are extremely rare ovarian tumors, and there is limited data available on their clinical characteristics and survival outcomes. Material and methods We conducted a historical cohort study of 56 patients to investigate their clinical characteristics. The overall survival, disease‐specific survival, recurrence‐free survival, and potential prognostic factors of these patients were also evaluated. Results The median age of these patients was 42.0 years (range: 20–71). The average mass and carcinoid size was 7.3 and 0.4 cm, respectively. Elevated tumor marker levels and ascites were observed in 15 and 10 patients, respectively. In 98.2% of the patients, tumors were confined to the ovary, while only one had metastatic disease. Surgery was the mainstay therapy: 37.5% of the patients underwent unilateral salpingo‐oophorectomy, 25.0% underwent hysterectomy with bilateral salpingo‐oophorectomy, 21.4% underwent ovarian cystectomy, 10.7% underwent comprehensive staging surgery, and 5.4% underwent bilateral salpingo‐oophorectomy. Appendectomy and lymphadenectomy were performed in eight and five patients, respectively, but none showed tumor involvement. Chemotherapy was the only adjuvant treatment utilized, and was administered in four patients. Pathological analysis showed that strumal carcinoid was the most predominant subtype, occurring in 66.1% of the patients. The Ki‐67 index was reported in 39 patients, 30 of which had an index of no more than 3%, with a maximum of only 5%. Only one relapse occurred after the initial treatment, and that patient experienced recurrences on two occasions, maintaining stable disease after surgery and octreotide therapy. After a median follow‐up of 3.6 years, 96.4% of the patients achieved no evidence of disease, while 3.6% were alive with the disease. The 5‐year recurrence‐free survival rate was 97.9% and no death occurred. No risk factors for recurrence‐free survival, overall survival, or disease‐specific survival were identified. Conclusions The Ki‐67 indices were extremely low and prognoses were excellent in patients with primary ovarian carcinoids. Conservative surgery, especially unilateral salpingo‐oophorectomy, is preferred. Individualized adjuvant therapy may be considered for patients with metastatic diseases.